A fenomênica do espaço presente nas violências : homofobia familiar e existência lésbica - Oliveira, Rayane Dayse da Silva (2024)
This thesis presents a qualitative and analytical study, referenced in the sociological debate, which mobilizes the intersectional approach to understanding familial homophobia and lesbian existence based on the intersection of gender and sexuality markers. The focus is on the lesbian issue and these women's experiences with homophobic violence, with emphasis on the domestic-familial context. Considering the narratives, contexts, and conflicts of lesbians, the subjects of this research, and the family as the locus of analysis, the thesis begins with the presentation of theoreticalmethodological issues related to the epistemological field and the central concepts of this study, such as homophobia, gender and sexuality, the phenomenics of space, family, and intersectionality, in addition to methodological considerations that include the presentation of the field and the profile of the research interlocutors. Next, we present some reflections on the lesbian issue, discuss the particularities of lesbophobia, and present an overview of academic production on the lesbian issue in Brazil in the last two decades (2001 – 2021). Next, we discuss what constitutes familial homophobia and how this form of violence affects lesbians, including a debate on the intensification of domestic violence during the Covid-19 pandemic and a brief discussion about the singularities of this phenomenon in the context of the United States, place where the concept of familial homophobia emerged and also where we carried out a Doctoral Internship Abroad (Doutorado Sanduíche). Finally, we present the lesbian narratives based on the speeches and life stories of our interlocutors, which include related elements to their identities, processes of affirmation, and experiences with violence, analyzed in light of critical theories of gender and sexuality.